Response of Sugarcane Rhizosphere Bacterial Community to Drought Stress - Liu, Qi; Zhao, Xiaowen; Liu, Yue; Xie, Sasa; Xing, Yuanjun; Dao, Jicao; Wei, Beilei; Peng, Yunchang; Duan, Weixing; Wang, Ziting (Frontiers in Microbiology, 2021)
Sugarcane is an important sugar and energy crop, whose yield has been gradually affected by frequent drought events. Although rhizosphere microorganisms can help in improving plant adaptation to the environmental stresses, little is known about sugarcane rhizosphere drought-resistant flora. Therefore, in this study, we aimed to analyze the changes in rhizosphere bacteria of different sugarcane cultivars under drought stress and explore their corresponding response mechanism. Three sugarcane cultivars, GT21, GT31, and GT42, which are widely cultivated in Guangxi, China, were exposed to drought stress and normal irrigation. The rhizosphere bacterial community structure and core functional bacteria in different treatments were analyzed by 16S rRNA sequencing technology, and the response of sugarcane rhizosphere bacterial community to drought stress was explored by examining soil enzymatic activity, soil nutrient content, and sugarcane drought-resistant traits. Finally, the response path of the sugarcane rhizosphere core functional bacteria under drought stress was demonstrated using structural equation modeling. The results showed that the changes in sugarcane rhizosphere bacteria under drought stress were related to the drought tolerance of sugarcane cultivars, and the changes were more evident in drought-resistant functional bacteria in the sugarcane rhizosphere of water-sensitive cultivars. Rhizobiales and Streptomycetales were directly affected by soil available phosphorus, soil urease, and soil acid protease, and regulate the drought tolerance of sugarcane. These results contribute to the understanding of the response mechanism of sugarcane rhizosphere bacteria to drought stress and provide a strong scientific basis for the implementation of microbial strategies to improve plant drought resistance.